Implementation Of The Ship Crew Recruitment And Selection Process At PT Ponti Sarana Utama - Farah Hasna Dzahabiyyah; Alldila Nadhira Ayu Setyaning (International Journal of Education, Vocational and Social Science, 2024)
Human Resources are an important asset for a company, therefore companies must pay attention to the employee recruitment and selection process. The aim of this research is to analyze the recruitment and selection process for ship crew as well as the obstacles faced in the recruitment process at PT Ponti Sarana Utama. This research used a qualitative method conducted by interviews with the crewing/personnel division and ship crew. Data collection was carried out through observation, interviews and documentation. This research shows that the recruitment system used only uses internal sources and closed methods. The selection process begins with checking documents, interviews, medical tests, then making a sea work agreement. The implementation of ship crew recruitment at PT Ponti Sarana Utama contained several obstacles which resulted in delays in ship crew recruitment. Some of the problems that occur are document discrepancies, crew certificates that have expired and are close to expiring before the contract period ends. Because the company carries out the recruitment process using internal sources, it can cause difficulties in finding the right candidates to fill the positions needed in the company.